TRADUÇÃO COMENTADA DO CONTO FOLCLÓRICO JAPONÊS “CHIKARA TAROU”, DE KEISUKE NISHIMOTO - FAÇANHA, SAMUEL ISAAC ESPINOZA (2018)
This work consists of an annotated translation of the Japanese folklore’s short story “Chikara Tarou”, by Japanese author Keisuke Nishimoto, from Japanese language to Brazilian Portuguese language. The research aims to contribute to the Japanese Literary Translation Studies through an analysis of linguistic and cultural aspects presented in the source text, as well as its consequences in the target culture and language, theoretically based on Venuti’s (2004) concepts of foreignization and domestication. Furthermore, this monograph seeks to disseminate the Mukashi-banashi literary genre and the short story, not yet translated in Brazil, providing knowledge concerning the author, genre, Japanese culture. In addition, it is as an attempt of deconstructing sexism presented in the short story through its annotated translation.